Jamaica : Request for an Arrangement Under the Extended Fund Facility. (IMF Staff Country Reports; Country Report ;, 2013)
During the past three decades, Jamaica has shown low economic growth and high public debt, and has faced other social challenges. To help restore competitiveness and improve financial market conditions, the authorities have come up with a comprehensive four-year economic program-2013/14 through 2016/17-that aims to avert immediate crisis risks and create the necessary conditions for sustained growth. The program's main pillars include structural reforms, fiscal adjustments supported by extensive fiscal reforms, and improved social protection programs.